Cord Blood Mononuclear Cells Have a Potential to Produce NK Cells Using IL2Rg Cytokines - Khaziri, Nahid (Adv Pharm Bull, 2016)
Purpose: Although bone marrow represents the main site for NK cell development and also distinct thymic-dependentNK cell pathway was identified, the cytokines effect on the NK cell generation from cord blood is unclear. Studies were identified the role of cytokines in the regulation of bone marrow and thymic NK cells. Previous studies reported that IL15 are critical for bone marrow dependent and IL7 is important for thymic NK cells. It is remain unclear the cytokines influence on the expantion of NK cells in cord blood mononuclear cells. Methods: We evaluated cultured cord blood mononuclear cells suplememnted with combinations of cytokines using FACS in distinct time points. In this study, we presented the role of IL2, IL7 and IL15 as members of the common gamma receptor -chain (Il2rg) on the expansion NK cells from cord blood cells. Results: By investigating cord blood mononuclear cells in vitro , we demonstrated that IL2 and IL15 are important for expansion of NK cells. IL2 in comparision with IL15 has more influences in NK cell expansion. In contrast IL-7 is dispensable for NK cell generation in cord blood. Conclusion: Thus,IL-2Rg cytokines play complementary roles and are indispensable for homeostasis of NK cell development in cord blood. Probably these cytokines could help to use NK beneficials in engrafment of transplanted cells and Anti tumor activity of NK cells.